Novitsky Vyacheslav Viktorovich (to 70th birthday) - O. I. Urasova; S. A. Nekrylov (Бюллетень сибирской медицины, 2016)
The biography of famous native scientist, doctor of medical sciences, academician of the Russian Academy of Sciences, head of Pathophysiology Department of Siberian State Medical University Professor V.V. Novitsky, has been prezented. The main directions of scientific and public activity of the scientist are shown.